(untitled) (Fiep Bulletin - online, 2014)
The importance of sport and leisure as coadjutors in the protection of young people and children has been emphasized mainly by their values, competitiveness and above all as a possibility to eradicate labor in childhood. This study aims to check by means of a documentary and a qualitative inquiry with exploratory and descriptive tenor sport and leisure activities as agents to favor eradication of labor in childhood. For that they have joined data together with analysis of inscription form documents of participants registered in sports and leisure projects at SESI - Unity Portão of Curitiba City. This research will check data referring to age group, object of this study; as well as if those people were in school or not; the time of entry into sporting and leisure practices and if their parents were industry workers or not. Thus, they have concluded that sport and leisure activities offered by SESI by means of its multiple options are able to fortify and to structure fight against labor in childhood